Quantification of CO2-cement-rock interactions at the well-caprock-reservoir interface and implications for geological CO2 storage. (August 2017) - Xiao, Ting; McPherson, Brian; Bordelon, Amanda; Viswanathan, Hari; Dai, Zhenxue; Tian, Hailong; Esser, Rich; Jia, Wei; Carey, William
Highlights: Wellbore integrity under CO2 -rich conditions is analyzed within an operational time scale. Cement tortuosity and diffusion coefficient are key parameters for determining the depth of the carbonation zone. A wellborn will maintain its integrity under the simulated conditions. Leaked brine salinity does not significantly impact CO2 -cement interactions. Abstract: Wellbore integrity is a key risk factor for geological CO2 storage. A primary purpose of this study is to analyze the impacts of CO2 leakage through wellbore cement and surrounding caprock with a gap (annulus) in between. Key parameters for cement-CO2 interactions were verified with a cement core sample from the SACROC Unit exposed to CO2 for 30 years. These parameters and other data served as the basis of reactive transport model simulations. The case study example for this analysis is the Farnsworth CO2 enhanced oil recovery (EOR) unit (FWU) in the northern Anadarko Basin in Texas. Specific objectives of this study are: (1) to analyze impacts on wellbore integrity under CO2 -rich conditions within an operational time scale; and (2) to predict mechanisms of chemical reactions associated with cement-CO2 -brine interactions. Simulation results suggest that cement tortuosity and diffusion coefficient are the two most important parameters that dictate cement carbonation penetration distance. Portlandite (Ca(OH)2 ) reacts with CO2 and forms calcite, reducing porosity, in turn directly impacting CO2 leakage rates by infilling pathways. Simulated calcium-silicate-hydrate (CSH) degradation is limited, suggesting that a wellbore will maintain its integrity and structure under the considered conditions. Simulations also suggest that sulfate concentration <2500 mg/L in the leaking brine would not cause monosulfate degradation. Without an existing fracture, CO2 will likely not enter the caprock, and the cement would not degrade accordingly. For the FWU specifically, the wellbore cement would likely keep its structure and integrity after 100 years. However, if a fracture exists at the cement-caprock interface, calcite dissolution in the limestone caprock fracture could occur and increase the fracture volume, a concern for caprock integrity.